Harnessing Digital Banking Technologies: Law as a Catalyst for Societal Progress and Economic Empowerment - Wellalage Indira Nanayakkara (Science and Technology: Developments and Applications Vol. 7, 2025)
In today’s digital era, the banking sector is evolving rapidly due to technological advancements, offering enhanced convenience, accessibility, efficiency and security to individuals and businesses. To ensure these technologies benefit everyone, it is important to have stringent laws that promote societal progress and economic empowerment. The law can act as a catalyst for positive change by ensuring equitable access to banking services and safeguarding against risks associated with technological advancements. The purpose of this research is to investigate how the utilization of digital technologies can be used in banking to improve the accessibility, quality and effectiveness for customers. In this context, law plays a key role in facilitating the development of banking to meet society’s needs in a sustainable, inclusive, and harmonious manner. The study emphasizes the role of law in facilitating rapid technological advancements in banking and explores the importance of regulatory frameworks in enabling innovation while ensuring that the pace of technological change is reasonable and that risks are minimized. The study highlights the need for vigorous data protection laws, e-commerce and cybersecurity standards that promote trust in digital banking systems and protect against cyber threats and criminal activities. Furthermore, the importance of laws prohibiting discriminatory practices and mandating accessibility standards in digital banking is discussed to ensure equal access for all segments of society, including those with disabilities. Ethical guidelines are proposed to address concerns about the development and use of banking technologies, while legal frameworks should prohibit unfair practices and empower customers through financial education initiatives. The research highlights major cybersecurity and data protection issues in Sri Lanka’s digital banking, calling for stricter law enforcement of existing laws and alignment with international standards. It also emphasizes the need for operational and technical solutions, while ensuring financial inclusion for underprivileged and disabled individuals. This study employs a library research methodology to examine the societal and individual impacts of DB technologies in Sri Lanka, analyzing existing literature and the legal framework to identify trends, challenges, and key factors influencing their adoption and implications for financial inclusion, social equity, and economic empowerment.